'Performance' as Cryptonymy : The Economy of Failure in Critical Theory - Čale, Morana (2009)
Although keyterms are supposed to perform an operatively compliant adequacy to the phenomena they refer to and to the specialist disciplines by which these phenomena are being studied, they may happen to take over the control of the disciplinary field by displaying a performative ability to rearrange, expand or restrict the subject matter that it discusses, hence to complicate, or render contradictory, the basic assumptions the research area is built upon. This ability, in our case concerning the word ‘performance’ as keyterm, derives from anasemia (or cryptonymy, or semantic conversion), the “strange foreignness [which] inhabits the same words” (Derrida), making them mean and rule out what they mean at once. Indeed, ‘performance’ relates to an artistic action capable of commenting upon its own medium and reflecting the process of its own actual being performed and received, that is, focused on establishing a position of representational alterity with respect to the pragmatic purposes of empirical reality ; at the same time, by indicating an ‘action being done’, it also designates an ‘action being done properly’, aiming at an efficient accomplishment, the achievement of a goal, in the sense of an investment supposed to bring about a profit. In other words, while meaning an activity emphasizing the process of its own coming into being as performance, as other to the seriousness of factual experience, the same word, by implying a semantic component of pragmatic result as opposed to a lack of performance, or to a misperformance, reframes the concept of performative effect in terms of economical effectiveness. In the context of performance studies, therefore, the two meanings of ‘performance’ operate in a sort of mutual negation, in an internal tension caused by two different, but intertwined economies.
Projekt MZOS
ENG